INCIDENCE, INDICATIONS, RISK FACTORS, AND OUTCOMES OF EMERGENCY PERIPARTUM HYSTERECTOMY WORLDWIDE: A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: The objective of this study is to provide a comprehensive analysis of the occurrence, indications, risk factors, outcomes, and management strategies associated with emergency peripartum hysterectomy on a global scale. Additionally, this study aims to compare the outcomes of this procedure across various income situations.Methods: A systematic search strategy was conducted across several electronic reference databases: PubMed, MEDLINE, EMBASE, ClinicalTrials.gov, Cochrane Library, Web of Science, and Emcare databases up to August 3, 2023. Duplicate publications, review articles, editorials, and incomplete articles were excluded.Results: This study presents an updated version of a previously conducted systematic review, which was originally published in 2016. The inclusion criteria for this study encompassed reports that provided data on the occurrence of emergency peripartum hysterectomy. Emergency peripartum hysterectomy was operationally defined as the surgical extraction of the uterus due to severe obstetric problems within a period of up to 6 weeks following childbirth. The process of title and abstract screening, as well as full-text review, was conducted with Endnote data management software. Out of a total of 8,775 papers that were reviewed, a subset of 26 articles published after the year 2015 were deemed eligible for inclusion. Consequently, the overall number of studies included in the analysis amounted to 154.Conclusion: There are significant variations in the occurrence of emergency peripartum hysterectomy across different income contexts. Women residing in lower-income settings face an elevated likelihood of experiencing emergency peripartum hysterectomy, as well as a greater burden of associated morbidity and mortality. The incidence of emergency peripartum hysterectomy is expected to rise because to the escalating prevalence of caesarean deliveries.